2010
DOI: 10.1002/ajmg.a.33331
|View full text |Cite
|
Sign up to set email alerts
|

Additional clinical and molecular analyses of TFAP2A in patients with the branchio‐oculo‐facial syndrome

Abstract: The branchio-oculo-facial syndrome (BOFS) is a rare disorder with approximately 50 sporadic and familial cases in the literature. We report on the clinical and molecular analyses of five additional patients with BOFS (two familial and three sporadic). DNA analysis of the TFAP2A gene associated with BOFS using DNA sequencing detected a mutation [c.763A>G (p.Arg255Gly)] in two unrelated patients. This mutation had been reported in another patient and indicates a probable mutational hotspot in the TFAP2A gene. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 22 publications
(37 reference statements)
0
13
0
Order By: Relevance
“…We originally described five families with BOFS that had heterozygous mutations or a deletion of the TFAP2A gene [Milunsky et al, 2008]. Four research groups have confirmed our original findings [Gestri et al, 2009; Stoetzel et al, 2009; Tekin et al, 2009; Reiber et al, 2010a]. This article extends ongoing clinical and molecular research to include 30 BOFS families (41 affected individuals), the largest series involving this syndrome.…”
Section: Introductionmentioning
confidence: 54%
See 2 more Smart Citations
“…We originally described five families with BOFS that had heterozygous mutations or a deletion of the TFAP2A gene [Milunsky et al, 2008]. Four research groups have confirmed our original findings [Gestri et al, 2009; Stoetzel et al, 2009; Tekin et al, 2009; Reiber et al, 2010a]. This article extends ongoing clinical and molecular research to include 30 BOFS families (41 affected individuals), the largest series involving this syndrome.…”
Section: Introductionmentioning
confidence: 54%
“… 1 Milunsky et al [2008]; 2 Mégarbané et al [1998]; 3 Lin et al [1995]; 4 Lin et al [2009]; 5 Gestri et al [2009]; 6 Stoetzel et al [2009]; 7 Tekin et al [2009]; 8 Reiber et al [2010]; 9 the senior authors (J.M. ; A.L.)…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…b Schematic representation of the human TFAP2A gene and mutations. Previously reported mutations (Reiber et al 2010; Gestri et al 2009; Tekin et al 2009) are shown with black arrows ; the position of the c.1025+2T>A mutation is shown with a red arrow …”
Section: Figmentioning
confidence: 99%
“…Interestingly, BCOR is a regulator of the transcription factor AP-2 (Fan et al, 2009). Mutations or deletions in the AP-2_ gene TFAP2A cause branchiooculofacial syndrome (BOFS) (MIM# 113620) (Milunsky et al, 2008; Reiber et al, 2010), which includes orofacial clefting, ocular anomalies and other facial dysmorphisms. It is possible that the presence of the different forms of oral clefts in OFCD is regulated by functional polymorphisms in TFAP2A or in AP2-regulated genes such as IRF6 (Rahimov et al, 2008).…”
Section: Discussionmentioning
confidence: 99%